2010
DOI: 10.1080/02626667.2010.489797
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of sediment rating curves for a deciduous forest watershed in Iran

Abstract: The suspended sediment load in a river is an indicator of its health. Yet, the direct measurement of suspended sediment load is difficult. Most assessments of suspended sediment load are therefore estimated from relationships developed between suspended sediment concentration and discharge, as sediment rating curves. However, these are not able to provide sufficiently accurate results. The present study aimed to assess the accuracy of the sediment rating curve in the educational forest watershed of Tarbiat Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…SL analysis, however, indicated that precipitation had the greatest impact on the amount of SL in the Kojour forest watershed, which agreed with Lana-Renault and Reg€ u es [35]. Furthermore, SL has been strongly influenced by human interferences such as sand and gravel mining in addition to precipitation and river hydrological conditions, which was similarly reported by Sadeghi and Saeidi [46] in the same watershed, Jabbari and Farzi [58] in Razavar River, Iran, and Sracek et al [59] in Kafue River, Zambia.…”
Section: Temporal Variation Of Suspended Loadsupporting
confidence: 84%
“…SL analysis, however, indicated that precipitation had the greatest impact on the amount of SL in the Kojour forest watershed, which agreed with Lana-Renault and Reg€ u es [35]. Furthermore, SL has been strongly influenced by human interferences such as sand and gravel mining in addition to precipitation and river hydrological conditions, which was similarly reported by Sadeghi and Saeidi [46] in the same watershed, Jabbari and Farzi [58] in Razavar River, Iran, and Sracek et al [59] in Kafue River, Zambia.…”
Section: Temporal Variation Of Suspended Loadsupporting
confidence: 84%
“…The high correlations between TF and gross precipitation have already been reported by former researches (e.g., Carlyle-Moses, 2004;Gurav et al, 2012;Park and Cameron, 2008;Shachnovich et al, 2008) as 0.998, 0.988, 0.996 and 0.979, respectively for different forest stands throughout the globe. The correlation results also showed that the influence of canopy cover to absorb the rainfall was significant just for rain events smaller than 30 mm.…”
Section: Discussionmentioning
confidence: 56%
“…Improving our understanding about rainfall partitioning in forests ecosystems is very important for studies that focus on forest hydrology to better management and decision making on this vital ecosystems (Ajami et al, 2011;Brecciaroli et al, 2012;Davudirad et al, 2015;Dohnal et al, 2014;Frot et al, 2007;Holko et al, 2009;Xu et al, 2014). Such eco-hydrological studies lead to a proper hydrological balance analysis and therefore have been well considered in forest hydrology studies during last few decades (Adriaenssens et al, 2012;Bosch and Hewlett, 1982;Carlyle-Moses, 2004;Devlaeminck et al, 2005;Gurav et al, 2012;Marin et al, 2000;Llorens and Domingo, 2007;Mitchell et al, 1986;Molina and Campo, 2012;Nanko et al, 2006;Park and Cameron, 2008;Rahmani et al, 2011;Shachnovich et al, 2008;Tcherepanov et al, 2005;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haregeweyn et al, 2012;Vanmaercke et al, 2014) or from data on sediment concentration in streamflow (e.g. Ulke et al, 2009;Sadeghi and Saeidi, 2010) or can be predicted with models (e.g. Walling et al, 2001;De Vente et al, 2013).…”
Section: Introductionmentioning
confidence: 99%